USE OF DARBEPOETIN ALFA (ARANESP®) FOR ANEMIA TREATMENT IN CHILDREN WITH CHRONIC KIDNEY DISEASE - CLINICAL EXPERIENCE OF BULGARIAN PEDIATRIC GROUP - Maria Gaydarova; Anelia Boueva; Svetlana Marinova; Galina Zlatanova (Peytchinski Publishing, 2017)
Darbepoetin alfa (DA) is indicated for treatment of symptomatic anemia related to chronic kidney disease (CKD) in adult and pediatric patients. In comparison with the recombinant human erythropoietin (rHuEpo), darbepoetin alfa has two additional carbohydrates containing sialic acid which prolong its half-life and enhance its biological activity in vivo. Herein, our clinical experience of using darbepoetin alfa (s.c.) for treatment of anemia in seven pediatric non-dialysis patients is presented. Subjects, aged 3-16 years were receiving (DA) for the period of 5 to 34 months to achieve and maintain hemoglobin levels between 100 and 120 g/l. Our secondary purpose was to establish whether the use of DA in children would reduce the frequency of painful injections, when administered subcutaneously, and improve the compliance of treatment. The early response of darbepoetin therapy was hemoglobin levels between 107 and 124 g/l. The subcutaneous administration of DA resulted in 2 dose corrections and showed that 86% of subjects achieved Hb level between 100 and 120 g/l.